Penguatan Literasi Trinitarian Berbasis Kajian Eksegetis Ulangan 6:4 Kepada Jemaat GBI My Home Tanjung Uban - Candra Gunawan Marisi; Elia Tambunan; Ardi Lahagu; Jabes Pasaribu; Upa Silaen; Aprilius Nahak; Rachmat Tony Sinjo Bantaeng; Wilma Sance Pattiasina; Didimus Sutanto B Prasetya (Sekolah Tinggi Teologi Gereja Kalimantan Evangelis, 2026)
This article analyzes a Community Service Program carried out by the Master of Theology Study Program of STT Real Batam at GBI My Home Tanjung Uban Kota on 24 to 26 January 2026 as a model for the downstream transfer of Trinitarian research grounded in the exegetical study of Deuteronomy 6:4. The approach employed is community-based participatory research, utilizing theological seminars, Bible study, interactive discussion, and doctrinal mentoring. The analysis demonstrates that translating the results of lexical and grammatical exegesis of the concept of eḥāḏ into the catechetical space of the congregation produces a significant strengthening of Trinitarian literacy, particularly in distinguishing the complex oneness of God from both tritheistic and modalistic misconceptions. The findings affirm that the downstream transfer of theological research is not merely a dissemination of knowledge but a formative pedagogical process that strengthens the hermeneutical capacity of congregants in responding to contemporary theological challenges. The article contributes by formulating a model of research-based community engagement that integrates the framework of practical theology with the tradition of public theology within the context of local Indonesian congregations. Its practical implication calls upon theological higher education institutions to position community service as a strategic pathway for the transformation of theological knowledge, rather than treating it as a mere supplementary element of the Tri Dharma of Higher Education.